Święty Augustyn: Kazanie 19. wygłoszone w «Basilica Restituta» w dniu «munerum» - Libowski, Łukasz (Vox Patrum, 2023)
Translation into Polish with commentary of St. Augustine's Sermon 19 preached in the restored Basilica on a day of the games.